2020
DOI: 10.1161/strokeaha.120.029452
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin I and Incident Stroke in European Cohorts

Abstract: Background and Purpose: Stroke is a common cause of death and a leading cause of disability and morbidity. Stroke risk assessment remains a challenge, but circulating biomarkers may improve risk prediction. Controversial evidence is available on the predictive ability of troponin concentrations and the risk of stroke in the community. Furthermore, reports on the predictive value of troponin concentrations for different stroke subtypes are scarce. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“… 33 On the other hand, circulating cTnI can serve as a predictor of stroke, as observational studies have shown. 7 , 8 A novel biomarker-based stroke risk score with the introduction of cTnI was well calibrated and performed better than the extensively used CHA2DS2-VASc score. 10 Nowadays, developed biosensors for cTnI detection are being promoted to aid early management decisions in acute strokes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 33 On the other hand, circulating cTnI can serve as a predictor of stroke, as observational studies have shown. 7 , 8 A novel biomarker-based stroke risk score with the introduction of cTnI was well calibrated and performed better than the extensively used CHA2DS2-VASc score. 10 Nowadays, developed biosensors for cTnI detection are being promoted to aid early management decisions in acute strokes.…”
Section: Discussionmentioning
confidence: 99%
“…It is a protein found in the cardiomyocytes and released into the bloodstream following myocardial injury. Elevated circulating cTnI level has been associated with a high risk of ischemic stroke, with hazard ratios ranging from 1.14 to 2.99 per 1-SD increase in cTnI [7][8][9] in the general population. Furthermore, circulating cTnI has also been included in the ABC (age, biomarkers, clinical history) stroke score for predicting stroke in patients with atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated cTnI concentrations are associated with an increased risk of the incidence of stroke in the community, irrespective of the subtype. Adding cTnI concentrations to classical risk factors only modestly improved the estimation of the 10-year risk of stroke in the overall cohort, but might be of some value in individuals at an intermediate risk ( 56 ).…”
Section: Troponinsmentioning
confidence: 99%
“…The panel included serum levels of 8 experimental markers: angiopoietin-like protein 3 (ANGPTL3), proprotein convertase subtilisin/kexin type (PCSK9), circulating total nitrate and nitrite ions (NOx), endothelin-1, leptin, adiponectin, galectin-3, and cardiac troponin I (cTnI). Most of these markers were not extensively validated but were previously demonstrated to be associated with cardiovascular risk in numerous studies and are directly or indirectly related to various aspects of cardiovascular pathology 3 . ANGPTL3 and PCSK9 participate in lipoprotein metabolism, which is associated with atherogenesis and development of cardiovascular lesions 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%